The Impact Of Return On Asset(ROA), Return On Equity (ROE) And Earnings Per Share (EPS), On Stock Price In The Non Cyclical Consummer Sector Period 2017-2021 - Fatonah, Siti; Aryati, Ida; Damayanti, Ratna (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Determining the impact that earnings per share, return on assets, and return on equity have on the price of consumer staples in the period 2017-2021 This study was conducted as descriptiv quantification with secondary data type. A total is 59 consumer essential companies are listed on IDX. purposeful sampling. The data collection method used the annuall financial statement data documentation method. tested with multiple linear regression analyses. As a result, Return on Asset (ROA) has a signifficant and negative impact on stock prices, Return on Equity (X2) has a positive and significant effectt on the share price. In stock costs, Profit Per Offer (EPS) emphatically affects stock costs. The independent variables ROA, ROE, and EPS can account for 83.5 percent of the stock price, according to the coefficient of determination analysis results. Additionally, you can expand this concentrate by involving other free factors as there are then again other autonomous factors like resource turnover, DAR, DER, CR, TATO and others that can influence stock cost.. Keywords: Roa; Roe; Eps; Stock price